Electrolysers for the hydrogen revolution: Challenges, dependencies, and solutions - Dawud Ansari; Julian Grinschgl; Jacopo Maria Pepe (Stiftung Wissenschaft und Politik (SWP), 2022)
Due to Europe's gas crisis and the Russian invasion of Ukraine, ramping up the hydrogen market has become more urgent than ever for European and German policymakers. However, ambitious targets for green hydrogen present an enormous challenge for the European Union (EU) and its young hydrogen economy. Apart from the demand for electricity, there is above all a lack of production capacities for electrolysers. The envisioned production scaling of electrolysers is almost impossible to achieve, and it also conflicts with import efforts and cements new dependencies on suppliers of key raw materials and critical components. Although a decoupling from Russia's raw material supply is generally possible, there is no way for the EU to achieve its goals without China. Aside from loosened regulations and the active management of raw material supply, Europe should also reconsider its biased preference for green hydrogen.
Keywords: 320; Russia; Ukraine; EU; climate and energy policy; REPowerEU; electricity; electrolyser; raw material; nickel; platinum-group metals (PGMs); polymer electrolyte membrane (PEM)